The promise of cinema : German film theory, 1907--1933 - Kaes, Anton; Baer, Nicholas, 1985-; Cowan, Michael J., 1971- (Oakland : University of California Press, 2016)
Rich in implications for our present era of media change, The Promise of Cinema offers a compelling new vision of film theory. The volume conceives of "theory" not as a fixed body of canonical texts, but as a dynamic set of reflections on the very idea of cinema and the possibilities once associated with it. Unearthing more than 275 early-twentieth-century German texts, this ground-breaking documentation leads readers into a world that was striving to assimilate modernity's most powerful new medium. We encounter lesser-known essays by Béla Balázs, Walter Benjamin, and Siegfried Kracauer alongs.
17. H. Ste., The Cinematograph in the Service of Ethnology (1907) 18. O. Th. Stein, The Cinematograph as Modern Newspaper (1913-14) ; 19. Hermann Häfker, Cinema and Geography: Introduction (1914) ; 20. Yvan Goll, The Cinedram (1920) ; 21. Hans Schomburgk, Africa and Film (1922).
Online resource; title from PDF title page (EBSCO, viewed February 15, 2016).
Includes bibliographical references.
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Motion pictures -- Germany -- History -- 20th century; Film criticism -- Germany; Motion pictures -- History -- 20th century; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Critique cinématographique -- Allemagne; Cinéma -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- General; Film criticism; Motion pictures; Germany; Filmtheorie; 1900-1999; History